The analysis of the state of foreign trade in the republic of Tuva on the 2011-2015 time period - Oorzhak, Aygul M. (The New Research of Tuva, 2016)
The article examines one of the most important topics in socioeconomic development of the Republic of Tuva — the region’s foreign trade. There is a marked lack of research on the current foreign trade turnover of Tuva. We used statistical data provided by the Agency for Foreign Economic Relations of the Republic of Tuva and the Siberian Customs Directorate of Federal Customs Service to analyze the foreign trade turnover and commodity structure of exports and imports for the years 2011-2015. The statistical data are presented in charts, showing the dynamics of the trends observed. In Tuva, imports exceed exports, with the main articles of export being minerals and foodstuffs, and those of import, machinery, equipment and vehicles. Despite the fact that the Republic of Tuva is a border region, its foreign trade is the smallest in the Siberian Federal district. In foreign trade turnover per capita (the indicator used by the World Bank to measure the openness of the global market), the economy of the Republic of Tuva is relatively closed. The factors hindering the development of foreign trade include the absence of railways and a small number of enterprises exporting competitive goods.